An Unusual Clinical Presentation of Gastrointestinal Metastasis From Invasive Lobular Carcinoma of Breast - Bathmapriya Balakrishnan MD; Sufiya Shaik MD; Irina Burman-Solovyeva MD, FACP (SAGE Publishing, 2016)
Introduction . We present an unusual case of metastatic lobular breast carcinoma. Typical areas of metastasis include bone, gynecological organs, peritoneum, retroperitoneum, and gastrointestinal (GI) tract, in order of frequency. With regard to GI metastasis, extrahepatic represents a rare site. Case . Two years after being diagnosed with invasive lobular breast carcinoma, a 61-year-old female complained of 3 months of nonspecific abdominal pain and diarrhea. A colonoscopy revealed 5 tubular adenomatous polyps in the ascending and transverse colon. Contrast computed tomography (CT) of the abdomen and pelvis was done 7 months after the colonoscopy to further evaluate persistent diarrhea. The CT results were consistent with infectious or inflammatory enterocolitis. Despite conservative management, symptoms failed to improve and a repeat diagnostic colonoscopy was obtained. Random colonic biopsies revealed metastatic high-grade adenocarcinoma of the colon. Discussion . Metastatic lobular breast carcinoma to the GI tract can distort initial interpretation of endoscopic evaluation with lesions mimicking inflammation. The interval between discovery of GI metastasis and diagnosis of lobular breast cancer can vary widely from synchronous to 30 years; however, progression is most often much sooner. Nonspecific symptoms and subtle appearance of metastatic lesions may confound the diagnosis. A high index of suspicion is needed for possible metastatic spread to the GI tract in patients with a history of invasive lobular breast carcinoma. Perhaps, patients with nonspecific GI symptoms should have an endoscopic examination with multiple random biopsies as invasive lobular carcinoma typically mimics macroscopic changes consistent with colitis.